The Principal’s Role as a Change Agent in Building a Culture of Teacher Compliance with School Policies - Sisra Yosi; Mada Sutapa (Journal of Education and Teaching Learning, 2026)
This study aims to describe the principal’s role as a change agent, identify supporting and inhibiting factors, and analyze the principal’s strategies in strengthening teachers’ compliance with school policies. The research employs a qualitative approach and was conducted at a public junior high school in Pelangiran Subdistrict, Indragiri Hilir Regency. Data were collected through in-depth interviews, observation, and documentation, and analyzed using Miles and Huberman’s interactive model, with data validity ensured through source and technique triangulation. The results show that the principal acts as a change agent through role modeling, coaching, supervision, participatory communication, and teacher empowerment. Supporting factors include teacher commitment, a family-like work climate, simple reward systems, and the use of digital technology, while inhibiting factors comprise resistance to change, heavy workload, limited technological competence, and inconsistent rule enforcement. The strategies employed include strengthening role modeling, continuous coaching and supervision, proportional reward and punishment, optimization of information systems, and reinforcing a culture of mutual reminder. This study concludes that effective principal leadership can shift teacher compliance from mere formality toward compliance based on awareness and collective professional responsibility.